Marriage in the Perspective of Islamic Law: A Study on the Validity and Meaning of Marriage - Siti Nurbaya; Rizqiani Novita Sari; Nurjaya Nurjaya; Rifqi Rifqi; Sumarta Sumarta (Penerbit Hellow Pustaka, 2025)
This study examines the concept of munakahat (Islamic family law), focusing on the legal requirements (syarat), pillars (rukun), and underlying wisdom (hikmah) of marriage in Islam. Using a normative library research approach based on the Qur’an, Hadith, and scholarly opinions, the study finds that marriage in Islam is not merely a social contract but an act of worship with legal and moral implications. The validity of marriage requires the fulfillment of key elements, including eligible spouses, a guardian (wali), two witnesses, ijab kabul, and mahr. These components ensure both the legal legitimacy of the marriage and the protection of the spouses’ rights. Furthermore, marriage aims to establish a harmonious family characterized by sakinah, mawaddah, and rahmah, contributing to social and moral stability. This study highlights the importance of integrating legal norms and philosophical values in understanding Islamic marriage, particularly in contemporary contexts. It contributes to strengthening Islamic legal literacy in the field of munakahat.